Halal Logistics Practices: Logistics Service Provider Cases in Indonesia - Faridatus Saidah; Yuliani Dwi Lestari (UIN Sunan Gunung Djati Bandung, 2021)
This study examines critical factors in affecting halal business management, particularly challenges in Halal logistics implementation faced by the logistics service provider as well as its potential and opportunities for Halal based business in Indonesia. An In-depth, semi-structured interview is conducted to deepen the understanding and to provide detailed data of the study. The study found that there are several factors influencing halal logistics implementation. In terms of business strategy, there are external and internal factors that affect halal logistics practices. Such as market-driven, perception benefit of halal logistic certification followed by customer loyalty, challenges in implementing halal logistics, the complexity of operation halal logistics, and invariably regulation factors. All of those factors have become a prior factor in implementing halal logistics practices. The findings can provide a guideline in how to implement halal logistics practices in logistic service provider business, especially in transportation and warehousing process, along with the expected result for its business performance.